Liquid Chromatography-Mass Spectrometry of Sterols - William Griffiths (Encyclopedia of Lipidomics, 2017)
According to the Lipid Maps classification system sterols are a class of compounds based on the cyclopenatanoperhydrophenanthrene skeleton and include cholesterol and its cyclic precursors, steroid hormones, bile acids and the ring opened secosterol vitamin D3.